EFL Students’ Learning Strategies During Covid-19 Pandemic: A Comparative Study Between Urban and Rural School Settings - Ariawan, Soni (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2023)
The present research is a descriptive quantitative research design using a survey method. There are 30 items adapted and modified from the SILL (Strategy Inventory for Language Learning) theory used to measure students' strategies in learning English. There are two senior high school (SMA) and 2 junior high school (SMP) contexts or equivalent as the subject of this research, namely students who study in the city of Mataram (urban school setting) and outside the city of Mataram (rural school setting). There were 112 students who participated in this study. Data analysis was carried out by calculating the total score of each question to determine the percentage level of relevance of the statement to the student's condition. The results of this study indicate that the English learning strategies of students in the city and outside the city are almost the same where they use the six learning strategies. Affective strategies and metacognitive strategies remained as the most favorable learning strategies for the EFL students.